Female Leaders and Earnings Management: An Exploration of Chief Positions - Septian Bayu Kristanto; Sidharta Utama; Sylvia Veronica N.P. Siregar (The Indonesian Journal of Accounting Research, 2022)
Female leader affects earnings management and the quality of the financial report. This study wants to investigate the effect of female leaders on real earnings management. We use the nine chief positions with a female presence as a leader. The data were obtained from Indonesia's public listed company on the S&P Global Market Intelligence database from 2012-2020. For real earnings management measures, we used data two years earlier. The data sample selected was 3.420 firm-year observations. The sample was separated into 12 classifications, according to IDX Industrial Classifications. Female leader positions as chief executive, chief accounting, and chief administration negatively affect real earnings management. While female leader positions as chief technology and chief marketing have a positive effect on real earnings management. We find that industrial has a different effect on real earnings management. Many studies are predicting female chief leaders and real earnings management. The most significant finding is female roles as finance managers. However, no research predicts real earning management using female leaders in various chief positions.